Studies on Beauveria bassiana isolated from the cocoa mirid, Helopeltis theobromae - Tong-Kwee, Lim; Muhamad, Rita; Fee, Chung Gait; Lan, Chin Chiew (Elsevier, 1989)
A white entomogenous fungus was found growing on Helopeltis theobromae, a serious pest of cocoa. With the aid of light and scanning electron microscopy techniques, the fungus was identified as Beauveria bassiana. The fungus grew and sporulated on several artificial media at temperatures between 5° and 30°C but not at temperatures higher than 35°C; it grew and sporulated best at 25°C. The fungus was highly pathogenic to Helopeltis adults which were sprayed or dusted with fungal spores.